INTRINSIC CARRIER CONCENTRATION AND THE FUNDAMENTAL HIGH-TEMPERATURE OPERATING LIMIT OF WIDE-BANDGAP SEMICONDUCTORS - M.Kh.Kuchkarov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The replacement of silicon by wide-bandgap (WBG) semiconductors such as 4H-SiC and GaN is the central trend in modern power and high-temperature electronics. Their advantage is governed by the equilibrium statistics of charge carriers: a doped device operates correctly only while the thermally generated intrinsic population n i remains far below the net doping. Using the classical nondegenerate carrier statistics, we compute n i (T) and the intrinsic-onset temperature T i on a common footing for Ge, Si, GaAs, 4H-SiC, and GaN with a temperature-dependent gap. At 300 K, n i spans about 23 orders of magnitude across the set, and T i (defined at a 10 16 cm −3 doping level) rises almost linearly with the band gap, reaching about 1550–1590 K for SiC and GaN versus 659 K for Si. The band gap is thus identified as the single dominant lever setting the fundamental high-temperature ceiling of a semiconductor device.